Case Report: Large Granular Lymphocyte Leukemia (LGLL)—A Case Series of Challenging Presentations - Pflug, Natali; Littauer, Annika; Beverungen, David; Sretenovic, Aleksandra; Wahnschaffe, Linus; Braun, Till; Dechow, Annika; Jungherz, Dennis; Otte, Moritz; Monecke, Astrid; Bach, Enrica; Franke, Georg-Nikolaus; et al. (Frontiers in Oncology, 2022)
Large granular lymphocyte leukemia (LGLL) represents a rare group of diseases with considerable difficulties in their correct diagnostic workup and therapy. The major challenges lie in their distinction from reactive (including autoimmune) lymphoproliferations. Moreover, monoclonal LGL proliferative diseases are in fact a heterogeneous group of disorders, as recognized by the three subtypes in the current WHO classification. It distinguishes two chronic forms (the focus of this case series), namely T-LGLL and chronic lymphoproliferative disorders of Natural Killer cells (CLPD-NK) as well as aggressive NK-cell leukemia. In the clinical routine, the variable presentations and phenotypes of T-LGLL and CLPD-NK are underappreciated. The relevant differential diagnoses range from benign reactive T-cell expansions to other mature T-cell leukemias to highly aggressive γδ-lymphomas. T-LGLL or CLPD-NK patients suffer from a wide variety of symptoms often including, but not limited to, cytopenias or classical autoimmune phenomena. They receive treatments ranging from mere supportive measures (e.g. antibiotics, growth factors, transfusions) over strategies of immunosuppression up to anti-leukemic therapies. The diagnostic pitfalls range from recognition of the subtle T-cell proliferation, repeated establishment of monoclonality, assignment to a descript immunophenotypic pattern, and interpretations of molecular aberrancies. Here, we report a series of selected cases to represent the spectrum of LGLL. The purpose is to raise awareness among the scientifically or practically interested readers of the wide variety of clinical, immunological, and phenotypic features of the various forms of LGLL, e.g. of T-cell type, including its γδ forms or those of NK-lineage. We highlight the characteristics and courses of four unique cases from two academic centers, including those from a prospective nationwide LGLL registry. Each case of this instructive catalogue serves to transport a key message from the areas of (chronic inflammatory) contexts in which LGLL can arise as well as from the fields of differential diagnostics and of various treatment options. Implications for optimization in these areas are discussed.